1994
DOI: 10.1002/pro.5560031109
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effects on protein structure examined by electrospray ionization mass spectrometry

Abstract: Electrospray ionization mass spectrometry (ESI-MS) has proven to be a useful tool for examining noncovalent complexes between proteins and a variety of ligands. It has also been used to distinguish between denatured and refolded forms of proteins. Surfactants are frequently employed to enhance solubilization or to modify the tertiary or quaternary structure of proteins, but are usually considered incompatible with mass spectrometry. A broad range of ionic, nonionic, and zwitterionic surfactants was examined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 33 publications
(50 reference statements)
1
158
0
1
Order By: Relevance
“…For example, the nonionic detergent, Triton X100, is widely used for the solubilization and characterization of the proteins. As mentioned before, in normal ESI the presence of surfactants such as Triton X100 in a protein sample solution leads to severe suppression of less solvophobic proteins [4]. If the sequential electrospray of analytes from more-surface-active analytes to less active ones occurs, the suppression effect could be largely moderated in PESI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the nonionic detergent, Triton X100, is widely used for the solubilization and characterization of the proteins. As mentioned before, in normal ESI the presence of surfactants such as Triton X100 in a protein sample solution leads to severe suppression of less solvophobic proteins [4]. If the sequential electrospray of analytes from more-surface-active analytes to less active ones occurs, the suppression effect could be largely moderated in PESI.…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants are frequently employed to enhance solubilization or to modify the tertiary or quaternary structure of proteins [4]. For example, the nonionic detergent, Triton X100, is widely used for the solubilization and characterization of the proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inheriting industrial-grade detergents such as SDS and Triton X-100, historically applied for cheap price, proteomics has suffered huge penalties in quality and cost. Using ESI MS experiments of intact model protein solutions (infusion and flow injection), a pioneering 1994 study reported several nonionic, zwitterionic, and anionic detergents tolerable by ESI MS, in acetic acid/ acetonitrile/H 2 O spray (top 7: n-dodecyl glucoside, n-hexyl glucoside, CHAPS, cholate, and three equally scored DDM, OG, and octyl thioglucoside), and in H 2 O spray (top 5: ndodecyl glucoside, n-hexyl glucoside, OG, n-octyl sucrose, and n-dodecyl sucrose) (71).…”
Section: Glucosides) Bp-1 Beta-strand Peptide Type 1 (N) Acetyl-(omentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T There is no universal detergent that can serve all the needs of proteomic research, and the choice of detergent selection is determined experimentally to suit the type of work to be carried out. However, the usage of detergents compromises with the MS analysis step to some extent due to-their interference in ionization step causing the shifts in charge-state distribution in ESI-MS [42]. Hence their removal prior to MS-analysis is essential, which can be achieved by different techniques such as dialysis, hydrophobic absorption, ultrafiltration, precipitation, gel filtration or solid phase extraction ( Table 1).…”
Section: Sample Preparationmentioning
confidence: 99%